Prospective Multicenter Study of Community-Associated Skin and Skin Structure Infections due to Methicillin-Resistant Staphylococcus aureus in Buenos Aires, Argentina - Lopez Furst, Maria Jose (2013)
Background. Community-associated methicillin-resistant Staphylococcus aureus(CAMRSA) is now the most common cause of skin and skin structure infections (SSSI) in several world regions. In Argentina prospective, multicenter clinical studies have only been conducted in pediatric populations. Objective. Primary: describe the prevalence, clinical and demographic characteristics of adult patients with community acquired SSSI due to MRSA; secondary: molecular evaluation of CA-MRSA strains. Patients with MRSA were compared to those without MRSA. Material and Methods. Prospective, observational, multicenter, epidemiologic study, with molecular analysis, conducted at 19 sites in Argentina (18 in Buenos Aires)between March 2010 and October 2011. Patients were included if they were ≥ 14 years, were diagnosed with SSSI, a culture was obtained, and there had no significant healthcare contact identified. A logistic regression model was used to identify factors associated with CA-MRSA. Pulse field types, SCCmec, and PVL status were also determined. Results. A total of 311 patients were included. CA-MRSA was isolated in 70% (218/311) of patients. Clinical variables independently associated with CA-MRSA were: presence of purulent lesion (OR 3.29; 95%CI 1.67, 6.49) and age <50 years (OR 2.39; 95%CI 1.22, 4.70). The vast majority of CA-MRSA strains causing SSSI carried PVL genes (95%) and were SCCmec type IV. The sequence type CA-MRSA ST30 spa t019 was the predominant clone. Conclusions. CA-MRSA is now the most common cause of SSSI in our adult patients without healthcare contact. ST30, SCCmec IV, PVL+, spa t019 is the predominant clone in Buenos Aires, Argentina.